ANALISIS YURIDIS PERBANDINGAN KEKUATAN HUKUM SISTEM INFORMASI PADA SENGKETA PEMILU 2019 DAN 2024 SERTA IMPLIKASINYA TERHADAP PASANGAN CALON PRESIDEN DAN WAKIL PRESIDEN - Bintang Tommy Rizaldy; Ruhtiani, Maya; Affrilies, Marlia Hafny (J-LEE - Journal of Law, English, and Economics, 2025)
This study discusses the comparison of the legal force of the Vote Counting Information System (Situng) in the 2019 Election and the Recapitulation Information System (Sirekap) in the 2024 Election and its implications for presidential and vice presidential candidate pairs. The main issues raised are unclear regulations, technical errors in data input, and the legal force of Situng and Sirekap in resolving election disputes. This study uses a normative legal method with a statute approach, case study approach, comparative approach, and conceptual approach. The results of the study show that neither Situng nor Sirekap have binding legal force on the final election results, but Sirekap has a stronger position because it can be used as supporting evidence if the C Result form is not available. However, both information systems are considered unable to fully realize the principles of justice, legal certainty, benefit, transparency, and accountability. And the implications are that the constitutional rights of presidential and vice presidential candidate pairs can be ignored, and public trust in the election results becomes vulnerable. Keywords: Legal Power, Election Information System, Election Dispute.